2017
DOI: 10.1016/j.bbmt.2017.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Stem Cell Transplantation with Myeloablative Conditioning Is Associated with Favorable Outcomes in Mixed Phenotype Acute Leukemia

Abstract: Mixed phenotype acute leukemia (MPAL) represents a poorly characterized group of acute leukemias that lack an accepted therapeutic approach and are typically associated with poor outcomes. We present our experience of genomic profiling, pre-transplant therapy and transplant outcomes for 36 well characterized pediatric and adult patients with MPAL defined according to the 2016 WHO leukemia update. A predominance of ALL-associated mutations and cytogenetic abnormalities was noted. Remission rates after induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Posttransplant outcomes of a subset of the patients were previously reported. 27 The clinical, morphologic, immunophenotypic, and cytogenetic/molecular results were independently re-reviewed by 2 hematopathologists (W.X. and M.R.).…”
Section: Methods Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Posttransplant outcomes of a subset of the patients were previously reported. 27 The clinical, morphologic, immunophenotypic, and cytogenetic/molecular results were independently re-reviewed by 2 hematopathologists (W.X. and M.R.).…”
Section: Methods Patientsmentioning
confidence: 99%
“…We have recently reported overall good outcomes in a well-defined cohort of MPAL patients undergoing allogeneic transplant, in contrast to prior studies, which were confounded by the inclusion of secondary AML cases. 27 Given the rarity of the disease and the evolving definition of this entity, the mutational repertoire of MPAL has not been fully elucidated. In addition, the mutations associated with specific lineage differentiation and the enrichment of mutations in specific cellular compartments have not been studied in MPAL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Reportedly, adults were transplanted in first remission, whereas children were transplanted in the setting of relapse or MLL rearrangement. 18 To date, clear distinctions are defined between strong and weak expression, as well as percentage requirements for positivity (especially, positivity for MPO). Using either definition of MPAL, ALL-therapy is associated with higher initial remission rates and is at least equivalent to more intensive AML therapy for long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Matutes et al reported a better complete remission rate (85%) with ALL-type therapy when compared with AML-type therapy (41%) [3]. Recent retrospective analyses showed favorable outcomes in MPAL patients consolidated with allogeneic hematopoietic stem cell transplantation (allo-HSCT) [12][13][14][15]. Blinatumomab, a bispecific CD19-directed CD3 T-cell engager, is a US FDA-approved drug for relapse and/or refractory (R/R) CD19 expressing B-ALL [16,17].…”
mentioning
confidence: 99%